Cytological evaluation of breast lesions in symptomatic patients presenting to Kenyatta National Hospital, Kenya: a retrospective study. Issue 1 (December 2015) - Nkonge, Ken; Rogena, Emily; Walong, Edwin; Nkonge, Dennis
Abstract Background Palpable breast lump, breast pain, and nipple discharge are common symptoms of breast disease. Breast cytology (fine-needle aspiration, nipple discharge smear, and touch preparation) accurately identifies benign, atypical, and malignant pathological changes in breast specimens. This study aims to determine the types of breast lesions diagnosed by breast cytology and assess the clinical adequacy of narrative reporting of breast cytology results. Methods Medical records of 390 patients presenting to breast or general surgery clinics in Kenyatta National Hospital, Nairobi, Kenya, between January 2010 and March 2014 were evaluated retrospectively. Results Of the 390 diagnosed breast lesions, 89.7 % (n = 350) occurred in females, while 10.3 % (n = 40) occurred in males, giving rise to a female-to-male ratio of 8.8:1. Neoplastic breast lesions (n = 296) comprised 75.9 %, while non-neoplastic breast lesions (n = 94) comprised 24.1 % of all diagnosed breast lesions. The neoplastic lesions were classified as 72.3 % (n = 214) benign and 27.7 % (n = 82) malignant, resulting in a benign-to-malignant ratio of 2.6:1. Fibroadenoma (n = 136) and gynecomastia (n = 33) were the most frequently diagnosed breast lesions for women and men, respectively. Conclusions Breast cytology effectively diagnosed neoplastic and non-neoplastic breast lesions. Neoplastic breast lesions occurred more frequently in women whereas non-neoplastic lesions occurred more frequently in men. To address the limitations associated with narrative reporting of breast cytology results, a synoptic reporting format incorporating the United Kingdom's National Health Service Breast Screening Programme's diagnostic categories (C1 to C5) is recommended for adoption by this hospital.